Взаємодія компонентів у системах AgSbP2Se6 – AgSbSe2 (Sb4(P2Se6)3) - Cабов Віктор; Victor Sabov; Поторій Марія; Potorij Mariia; Кітик Іван; Iwan Kityk; Філеп Михайло; Filep Mihály; Filep Mykhailo; Погодін Артем; Pogodin Artem; Сабов Мар’ян; et al. (ДВНЗ Ужгородський національний університет, 2019)
Резюме. Система Ag–Sb–P–Se характеризується наявністю в ній ряду складних напівпровідникових фаз. Серед них AgSbSe2, що утворюється у системі Ag2Se – Sb2Se3 і відноситься до відомого класу напівпровідникових сполук МеІВ VC VI 2 (MeI – Tl, Cu, Ag; BV – Sb, Bi; CVI – S, Se, Te). AgSbSe2 є вузькозонним напівпровідником, з високим коефіцієнтом термо-ЕРС та низькою теплопровідністю, кристалізується у структурному типі NaCl (просторова група (ПГ) F m-3m), де позиції атомів металу статистично заповнюють атоми аргентуму та стибію, плавиться конгруентно при 883 K [1, 2]. Останні роки значний практичний інтерес викликають тверді розчини на основі AgSbSe2, оскільки модифікацією елементного складу, зокрема частковою заміною стибію на станум чи плюмбум або селен на телур вдається покращити термоелектричну потужність матеріалів та/або змінити температурний інтервал максимального термоелектричного ефекту [3-5].

Abstract. The purpose of the study was to determine the interaction in the systems based on the compounds AgSbP2Se6 and AgSbSe2 (Sb4(P2Se6)3). To achieve the goal, 13 samples were synthesized in the AgSbP2Se6 – AgSbSe2(Sb4(P2Se6)3) systems. Synthesis was carried out in evacuated up to 0.13 Pa quartz ampoules. The initial materials were pre-synthesized AgSbP2Se6, AgSbSe2 and Sb4(P2Se6)3. Their synthesis was carried out from high purity elementary components taken in a stoichiometric ratio. The maximum temperature of synthesis was 40-50 K above the melting point of components, including the products of interaction. Homogenizing annealing was conducting at the temperature 573 K for 120 hours. The identification was carried out by differential thermal analysis (DTA) and Xray powder diffraction (XRD) (DRON 4.07, Cu Kα radiation). Synthesis of alloys was carried out in a similar way. The maximum temperature of the synthesis was 900 K. Annealing was carried out at 573 K for 240 hours. The obtained samples were investigated by DTA and XRD methods. The AgSbP2Se6 – AgSbSe2 system belongs to the eutectic type with boundary solid solutions based on the starting components. The solubility on the AgSbP2Se6 side is about 5 mol.%, and on AgSbSe2 – about 8 mol.%. The primary crystallization lines in the system intersect at the eutectic point with coordinates 724 K, ~ 33 mol.% AgSbSe2. The homogeneity region of AgSbSe2 with increasing temperature is strongly expanding and at an eutectic temperature up to 30 mol.%, whereas this is not observed for AgSbP2Se6. The synthesized samples in AgSbP2Se6 – Sb4(P2Se6)3 system were compact ingots with a rather dim metallic shine. The indexing of the X-ray powder diffractograms show that two phases AgSbP2Se6 and Sb4(P2Se6)3 are exist in the system. On the thermograms of samples two endothermic effects were observed. The temperature of the low-temperature endothermic effect practically did not change in the whole concentration range (5 – 95 mol.%), which indicated the eutectic interaction. Invariant eutectic point is located on the side of Sb4(P2Se6)3, its coordinates are 646 K, ~ 96 mol.% Sb4(P2Se6)3. The solubility areas based on the initial components at annealing temperature do not exceed 5 mol%.
Interaction in the AgSbP2Se6 – AgSbSe2 (Sb4(P2Se6)3) system
Keywords: диференціальний термічний аналіз; граничний твердий розчин